TINJAUAN YURIDIS PEMECAHAN TANAH LEBIH DARI LIMA BIDANG UNTUK HAK MILIK PERORANGAN - Yutanti, Trinda; Dewi Hariyana, Trinas; Wahid Hasyim, Moch. (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2024)
The emergence of a regulation of the Minister of Agrarian Affairs and Spatial Planning or the Head of the National Land Agency on the prohibition of land division of more than five parcels for individual property rights is a way to overcome the rampant housing or disguised lots that have sprung up so far. The regulation is stipulated in Regulation of the Minister of Agrarian Affairs and Spatial Planning or Regulation of the Head of the National Land Agency Number 16 of 2021 concerning the Third Amendment to Regulation of the Minister of Agrarian Affairs or Head of the National Land Agency Number 3 of 1997 concerning Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration. The purpose of this writing is to find out how the juridical review of land splitting of more than five parcels for individual property rights and what the legal consequences are for individuals who split more than five parcels of land. This research uses normative juridical approach with legislation. The result of this research is that the ownership of property rights to individual land or the division of individual land parcels is not allowed to exceed five parcels except if the base of the right comes from the transfer of inheritance rights or the base of the right with the building rights certificate. Apart from that, the division of more than five parcels must also be balanced with permits from the authorized agency, and usually with the base of the Building Rights Title, but in the current era there are still many Individual Property Rights whose ownership exceeds five parcels. However, with the emergence of the Regulation of the Minister of Agrarian Affairs and Spatial Planning or Regulation of the Head of the National Land Agency Number 16 of 2021, the regulation is more strictly applied in practice. Keywords: Land Division of More than Five Parcels, Agrarian.